Post-traumatic Stress Disorder Levels in Medical Students who Experienced Türkiye Kahramanmaraş 2023 Earthquake - Vedat Karataş; Elif Nur Yıldırım Öztürk (Sakarya Üniversitesi Holistik Sağlık Dergisi)
Objective: Earthquakes have significant effects on both physical and mental health. One of the mental health effects is post-traumatic stress disorder (PTSD). This study aimed to determine the level of PTSD and the variables associated with this level in a group of medical students who experienced the February 6, 2023 earthquake in Türkiye, centered on Kahramanmaraş. Method: The study was cross-sectional. Data from 40 medical students were evaluated. A 15-question data collection form and a 20-item scale for determining the level of post-earthquake trauma were used for the study. The scale provides scores ranging from 20 to 100, and an increase in the score indicates an increase in the level of trauma. In this study, the Pearson correlation coefficient and Cohen's d were calculated as effect sizes. Ethics committee approval and institutional approval were obtained for this study. Results: Twenty three of the students were male. Of the students, 31 had experienced loss of a loved one and 36 had experienced damage to residential building. The mean score of the students on the scale was 63.5±14.1. Gender (0.639), maternal education level (0.256), pre-earthquake income status (0.211), professional psychological support (0.785), loss of a loved one (0.166), damage to residential building (0.209), loss of property (0.544), and post-earthquake migration (0.399) were identified as variables associated with PTSD. Conclusion: Most students were negatively affected by the recent earthquake and experienced medium PTSD. It is important to provide community and risk group based mental health support after the earthquake.